2009
DOI: 10.1017/s0022112008004400
|View full text |Cite
|
Sign up to set email alerts
|

The effect of drainage on the capillary retention of CO2 in a layered permeable rock

Abstract: We examine the motion of a buoyant fluid injected into a water-saturated porous rock as it spreads along a thin inclined low-permeability barrier. We account for leakage of the fluid across the barrier once the current is sufficiently deep so that the pressure exceeds the capillary threshold. We show that at some distance from the source, the pressure decreases below this threshold, and all the remaining flux spreads laterally along the barrier. We examine the controls on the partitioning of the flow between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…Several factors control the extent of such drying out of the caprock. First, as the initially dry CO 2 is transported through the reservoir sand from the injector, water will evaporate into the CO 2 and the water saturation will increase (Gaus et al, 2008); second, when the CO 2 phase reaches the caprock in a stagnant plume, significant fractions of residual water within the plume will be available (Suekane et al, 2005;Farcas and Woods, 2008); and third, capillary suction forces of water in the caprock may not be strong enough to hold the water from the caprock even for a strongly waterundersaturated CO 2 plume. As we are not aware of any reports that verify the drying-out phenomena from natural reservoirs or from laboratory experiments, we leave this as an open question for further discussions.…”
Section: Discussion On Dry-outmentioning
confidence: 99%
“…Several factors control the extent of such drying out of the caprock. First, as the initially dry CO 2 is transported through the reservoir sand from the injector, water will evaporate into the CO 2 and the water saturation will increase (Gaus et al, 2008); second, when the CO 2 phase reaches the caprock in a stagnant plume, significant fractions of residual water within the plume will be available (Suekane et al, 2005;Farcas and Woods, 2008); and third, capillary suction forces of water in the caprock may not be strong enough to hold the water from the caprock even for a strongly waterundersaturated CO 2 plume. As we are not aware of any reports that verify the drying-out phenomena from natural reservoirs or from laboratory experiments, we leave this as an open question for further discussions.…”
Section: Discussion On Dry-outmentioning
confidence: 99%
“…[50] We point out these implications since it has been common to use this time rate of change as a simplified hysteresis model in the literature [Farcas and Woods, 2009;Hesse et al, 2008;Juanes et al, 2010;Kochina et al, 1983]. One study that accounts for the full hysteresis model in a sharp interface setting is reported by Juanes and Mac-Minn [2008].…”
Section: Effect Of Residual Trapping On Upscaled Equationsmentioning
confidence: 99%
“…The trapping of fluid by capillary forces at the pore scale is known to be important (Farcas & Woods 2009), and the unexpectedly large increase in the flux across the interface when it can deform even slightly suggests another key difference, since diffuse miscible interfaces may be more readily deformed than sharp immiscible interfaces. This indicates a potentially serious drawback of the miscible experimental systems that are most readily used as analogues for CO 2 sequestration problems (e.g.…”
Section: Futurementioning
confidence: 99%